Multisensory Integration: Brain, Body and the World - Achille Pasqualotto (Frontiers Research Topics, 2016)
Behaviour, language, and reasoning are expressions of neural functions par excellence, as the brain must draw on sensory modalities to gather information on the rest of the body and on the outer world. Cortical areas processing the identity and location of sensory inputs were once thought to be organised hierarchically, with some branches dedicated to basic features and other branches dedicated to complex features. Yet current studies have uncovered synergistic effects at early sensory cortices as well as at higher-level association areas. A less hierarchical functional architecture of the brain has emerged such that, irrespective of sensory modality, inputs would be allocated to the best suited cortical substrate. It is our hope that the articles included in this special issue will offer novel insights into recent developments relating to multisensory integration and brain functioning.